Characterization and comparison of high-modulus asphalt mixtures produced with different methods. (20th March 2020) - Yan, Jinhai; Leng, Zhen; Ling, Cheng; Zhu, Junqing; Zhou, Luxiaodong
Highlights: Performances of various high-modulus asphalt mixtures were evaluated. Rubberized asphalt mixture was found to provide the best overall performance. Three HMAMs were found to be good candidates for treating rutting problem. Abstract: It is well known that rutting is one of the major distresses for asphalt pavements. To enhance the rutting resistance of asphalt pavements, different approaches have been developed, among which using high-modulus asphalt mixtures (HMAM) has been proved effective. The main objective of this study is to characterize and compare the performances of using hard binders, HMAM additives, and polyester fiber, in producing HMAM. To achieve this objective, the rheological properties of four hard binders, including rubberized bitumen, lake bitumen and SBS collectively modified asphalt binder, rock bitumen and SBS collectively modified asphalt binder, and hard-grade asphalt binder, were first tested. Then, three modulus parameters, namely resilient moduli, dynamic moduli and stiffness moduli, of seven mixtures, including four mixtures prepared with the four hard binders, one SBS modified mixture, one SBS modified mixture with an HMAM additive, PR.M., and one SBS modified mixture with polyester fiber, were measured and compared, followed by comprehensive laboratory performance tests, including rutting resistance, low-temperature cracking resistance, fatigue resistance, and moisture damage resistance tests, and binder-mixture performance correlation analysis. It was found that all the four hard binders can produce mixtures with high modulus as expected. Among different mixtures, rubberized asphalt mixture was provided best overall performance. For the purpose of rutting treatment, rubberized asphalt mixture, the mixture collectively modified by SBS and rock bitumen, and the SBS modified asphalt mixture with PR.M. additive are the better candidates in consideration of their superior rutting resistance and relatively more balanced performance properties.